Prevalence of COVID-19 Incidence Rates in Hypertension Patients at Ibnu Sina Hospital Makassar in 2020 - Saputra, Pryantama; Wiriansyah, Edward Pandu; Ardiansar, Abdul Mubdi; Tulak, Sandy; Rahman, Rusman (Jurnal Biologi Tropis, 2024)
The COVID-19 virus, which is caused by SARS-CoV-2, is a global health problem that affects many nations. Similar to the H7N9, SARS, and MERS viruses, COVID-19 can be more severe in hypertensive individuals. With a prevalence of 50.1% among COVID-19 patients, hypertension is a significant comorbidity that increases the risk of death by 1.37 times due to the increased number of ACE2 receptors that facilitate the virus's spread. This study uses a descriptive cross-sectional design with secondary data from medical records of COVID-19 patients with hypertension at Rumah Sakit Ibnu Sina Makassar. Data were collected through total sampling after obtaining permission from the hospital and then processed and analyzed descriptively. The study shows that the majority of COVID-19 patients with hypertension are aged 65 and over (33.4%). Male patients are slightly more prevalent (53%) compared to females (47%), possibly due to genetic factors affecting the immune system. Seventy-three percent of patients adhered to hypertension treatment, while 27% did not. The function of the ACE-2 enzyme, which is also affected by antihypertensive treatment, may have an impact on the relationship between COVID-19 and hypertension. These findings emphasize the significance of treating the elderly and remaining on treatment in order to reduce the likelihood of contracting COVID-19. The survey derives that the vast majority of Covid patients with hypertension are developed 65 and over (33.4%), with an insignificantly higher inescapability of folks (53.3%) diverged from females. Adherence to hypertension treatment is high, with 73.3% of patients following their prescribed regimen.